2003
DOI: 10.1210/jc.2002-021215
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia Nervosa Is Characterized by Increased Adiponectin Plasma Levels and Reduced Nonoxidative Glucose Metabolism

Abstract: The aim of the present study was to examine the effects of anorexia nervosa (AN) on adipocytokines (leptin and adiponectin) plasma concentrations and insulin-stimulated glucose disposal in adolescent and young adult women. Adiponectin and leptin plasma levels, along with insulin-stimulated glucose disposal (as measured by the euglycemic-hyperinsulinemic glucose clamp) and oxidative and nonoxidative glucose metabolism (as measured by indirect calorimetry during the last 60 min of the insulin clamp), were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
4
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(92 citation statements)
references
References 38 publications
6
78
4
4
Order By: Relevance
“…These results are not in agreement with the study of Housova et al (2005), which did not observe any difference between R-AN and BP-AN forms. Other studies showed an increase in serum adiponectin levels in AN but did not deal with AN subtypes Pannacciulli et al, 2003). However, it is noteworthy that Monteleone et al (2003) documented a significant increase of circulating adiponectin levels in patients with bulimia nervosa and a correlation of this increased adipocytokine secretion with the frequency of binge/purge episodes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These results are not in agreement with the study of Housova et al (2005), which did not observe any difference between R-AN and BP-AN forms. Other studies showed an increase in serum adiponectin levels in AN but did not deal with AN subtypes Pannacciulli et al, 2003). However, it is noteworthy that Monteleone et al (2003) documented a significant increase of circulating adiponectin levels in patients with bulimia nervosa and a correlation of this increased adipocytokine secretion with the frequency of binge/purge episodes.…”
Section: Discussionmentioning
confidence: 93%
“…Serum adiponectin has been found to be either increased Pannacciulli et al, 2003), normal (Iwahashi et al, 2003) or decreased (Tagami et al, 2004) in AN patients. Likewise, serum plasma resistin levels have been found to be either decreased (Dostalova et al, 2006) or normal (Dolezalova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Adiponectin serum levels inversely correlate to body weight. Thus, low adiponectin levels are found in obesity, 10,11 and high levels are found in anorexia nervosa 12 and during weight loss. 13 Low adiponectin levels are also associated with insulin resistance and development of diabetes mellitus, 14 and administration of adiponectin is associated with increased insulin sensitivity and fatty acid catabolism.…”
mentioning
confidence: 95%
“…Disturbances in hormonal regulation or nutrition may increase the risk for NAFLD. For example, insulin resistance, occasionally seen in AN [9][10], increases peripheral fatty acid mobilization and decreases hepatic oxidation of fatty acids. Although the relationship between insulin resistance and NAFLD has been welldescribed in obese and normal-weight individuals [11], it has not been explored in AN.…”
mentioning
confidence: 99%